Endovascular Treatment of Ruptured Brain AVMs in the Acute Phase of Hemorrhage - van Rooij, W.J.; Jacobs, S.; Sluzewski, M.; Beute, G.N.; van der Pol, B. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Patients with ruptured brain AVMs are at considerable risk of repeat hemorrhage, particularly when associated intranidal or flow-related aneurysms are present. There is controversy about the timing of diagnosis and treatment of patients with hemorrhagic stroke. We present our results of endovascular treatment of ruptured AVMs in the acute phase. MATERIALS AND METHODS: Between January 2008 and March 2011, 23 patients (16 men, 7 women; mean age 42 years) with AVM-related hemorrhagic stroke were treated with endovascular techniques within 10 days of the ictus. There were 10 micro-AVMs (< 1 cm) and 1 single-hole pial fistula. In 9 patients, an intranidal or flow-related aneurysm was the likely cause of hemorrhage. RESULTS: Complete obliteration of the AVM with Onyx was achieved in 13 of 23 patients (57%). Eight of the 13 AVMs were micro-AVMs and 3 had an intranidal aneurysm. Partial obliteration of the AVM was achieved in 10 of 23 patients (43%). In 6 of these 10 patients, an intranidal (n = 1) or flow-related aneurysm (n = 5) was obliterated with Onyx or coils. There were no complications of treatment. During a mean follow-up of 21 months in 22 surviving patients, no repeat hemorrhage occurred. CONCLUSIONS: Endovascular treatment with Onyx in the acute phase cured most ruptured AVMs. All 9 AVM-associated aneurysms that were considered the source of hemorrhage could be excluded from the circulation. In patients with AVM-related hemorrhagic stroke, prompt angiographic diagnosis and treatment may improve prognosis by reducing repeat hemorrhage rate.